Independent prognostic impact of plasma NCOA2 alterations in metastatic castration‐resistant prostate cancer. Issue 13 (12th July 2021) - Fettke, Heidi; Kwan, Edmond M.; Bukczynska, Patricia; Steen, Jason A.; Docanto, Maria; Ng, Nicole; Parente, Phillip; Mant, Andrew; Foroughi, Siavash; Pezaro, Carmel; Hauser, Christine; Nguyen‐Dumont, Tu; et al.
Abstract: Background: The androgen receptor (AR) pathway‐associated gene nuclear receptor coactivator 2 ( NCOA2 ) has an established oncogenic role in early prostate cancer and likewise is a driver of metastatic disease and castration‐resistant prostate cancer. However, its significance as a biomarker in metastatic castration‐resistant prostate cancer (mCRPC), both alone and in conjunction with co‐occurring AR alterations using a liquid biopsy approach has not been investigated. Methods: Ninety‐one patients were included in this study, ( n = 68 receiving an androgen receptor pathway inhibitor and n = 23 receiving taxane chemotherapy). Up to 30 ml of peripheral blood was collected before commencing treatment from each patient. Plasma cell‐free DNA, along with a matched germline sample, underwent targeted next‐generation sequencing using a validated, highly sensitive in‐house prostate cancer panel. Variants in AR and NCOA2 were identified and correlated with clinical outcomes. Results: Plasma AR and NCOA2 aberrations were identified in 35% and 13% of the cohort, respectively, whilst 8% had concurrent AR and NCOA2 alterations. NCOA2 copy number gain and any NCOA2 aberration predicted for lower prostate‐specific antigen (PSA) response rates. Likewise, median overall survival was shorter for NCOA2 gain (10.1 vs. 18.3 months; p = .004), remaining significant after adjusting for covariates including circulating tumor DNA fraction and tumor suppressor gene alterations. Importantly, dual AR and NCOA2 aberrations were also associated with inferior outcomes, including no PSA responses in patients treated with AR pathway inhibitors (0% vs. 64%; p = .02). Conclusions: These data highlight the importance of identifying multiple markers of AR pathway modulation in mCRPC and represent the first instance of the assessment of plasma NCOA2 status as a prognostic biomarker for standard‐of‐care therapies. Further assessment is warranted to determine if NCOA2 aberrations are a marker of primary resistance to AR pathway inhibitors.